The awareness of online scam among teenagers / Iqbal Hakim Md Fisal - Md Fisal, Iqbal Hakim (2022)
Technology is evolving from time to time. Today, many people have used technology and taken advantage of the convenience from it. However, there are some people with bad intention who take advantage of the facilities available in technology today. Online scam is a cybercrime committed using technology through the internet. This illegal activity is easier to do than other crimes such as bank robbery and others. This is because they only need internet to start the process and it can do it anywhere. Therefore, the purpose of this study is to see to what the current level awareness of teenagers towards online scams. Structured survey questions were provided to teenagers who aged 16 to 30 years, with a total of 100 respondents in this study. The main goal of this study was to find out more about the level of their awareness about online scams and to warn them about the dangers of online scams. The findings of the study revealed that teenagers have a satisfactory level of awareness in online scams. Researcher believe that this research can be extended and applied to the public to prevent themselves from falling victim to online scams